O projeto Kantiano para a paz perpétua: pressupostos morais, jurídicos e políticos - Lima, Francisco Jozivan Guedes de (2012)
This research aims to investigate the kantian project Toward Perpetual Peace from its moral juridical and political presuppositions In Kant’s conception peace is an ideal unattainable but the fundamental principles directed to the approximation this ideal are historically possible Similar to individuals States in their mutual relations should to enter into a juridical condition Problems about the transitoriness of property freedom and violence will not be resolved unless the law be established also on the international and cosmopolitan level For the philosopher of Königsberg the constitution of each State must be republican because in the republicanism the decision on war is a prerogative of the citizens The Republican State thought by Kant can not force citizens go to war The citizens opt for peace because they don’t want to lose their life liberty security property and their rights In cosmopolitan law Kant criticizes the abuses of colonialism and accentuates the need of the respect to the right of the peoples Questions that deal with contemporary international relations such as peace treaties sovereignty public sphere Standing Armies right of interference cosmopolitanism and among others law of peoples will be addressed in this research Methodologically the research is divided into two parts one concerning to presuppositions of the Kantian project to perpetual peace and another that investigates the project itself starting the fundamental themes that are inserted in the preliminary articles in the definitive articles in the supplements and appendices.